The Influence of Hedonic Shopping Motivation and Price Discounts on Impulse Buying with Positive Emotion as an Intervening Variable among Shopee Users in Solo Raya - Redyawati, Adelia; Achmad, Nur (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Shopee is the most widely used e-commerce platform among Indonesians. Shopee makes it easy for users to buy products online, which encourages them to make unplanned or impulsive purchases. This study aims to analyze the influence of hedonic shopping motivation and price discounts on impulse buying, mediated by positive emotions, among Shopee users in Solo Raya.Methodology: This study uses a quantitative approach and data collection was carried out using non-probability sampling techniques with purposive sampling methods through the distribution of questionnaires using Google Forms. This study focused on 180 respondents who are Shopee e-commerce users in Solo Raya. Data analysis in this study was carried out using the PLS (Partial Least Square) method, which was processed using SmartPLS 4.0 software.Results: The results of this study indicate that hedonic shopping motivation and price discounts partially have a significant effect on impulse buying. Both variables also partially affect positive emotions significantly. However, positive emotions do not have a significant effect on impulse buying and do not mediate the effect of hedonic shopping motivation and price discounts on impulse buying. Applications/Originality/Value: This study provides strategic insights for Shopee e-commerce and Shopee sellers based in Solo Raya to focus on price discount and hedonic shopping motivation promotion strategies to encourage impulse buying.